Indigenous Cellulosic Raw Materials for the Production of Pulp, Paper and Board Part XXVIII. Wrapping Papers from Blue Gum (Euoalyptus owbulus Labill.) - Brat, R. V.; Gupta, P. R.; Kapur, R. L. (Indian Forester, 1956)
Laboratory experiments on the production of pulps from Blue gum (Eucalyptus globulus Labill.) by the sulphate and soda processes are described. One pilot plant experiment was carried out by the sulphate process and well-cooked pulp in 57.9% yield of light brown colour was obtained. Wrapping paper made from 100% Blue gum was characterized by good formation and satisfactory strength properties. Since Blue gum is short fibred, its pulp will require to be admixed with a suitable portion of a long-fib red pulp, such as bamboo pulp, for the manufacture of wrapping papers on commercial paper machines. A sample of the wrapping paper made on the pilot plant is included in this bulletin.